The changing intra-household resource allocation in Russia - Guy Lacroix; Natalia Radtchenko (Institute for the Study of Labor (IZA), 2008)
During the transition toward a market economy, Russian workers have had to face important structural changes in the labour market as well as dramatic changes in their real earnings. In the process, the wage gap between men and women has varied wildly over that period. In recent years, young women have embraced professional careers, are more mobile on the labour market, and tend to delay the birth of their first child. All these trends are likely to influence intra-household relations and consequently the family decision process. To investigate this matter, we estimate a household collective labour supply model. We generalize the specification so as to allow the sharing rule to change in a discrete manner between the pre and post 1998 financial crisis periods. The parameters of the sharing-rule indicate that the households have shifted to a new equilibrium in the post-1998 period. Indeed, husbands have become more egotistic and wives more altruistic: An increase in their relative wage translates into a smaller/larger transfer to their spouse.
urn:nbn:de:101:1-20081014382
Keywords: D1; 330; Collective model; sharing rule; Russian economic crisis; Haushaltsökonomik; Familienökonomik; Frauenerwerbstätigkeit; Arbeitsangebot; Männer; Übergangswirtschaft; Wirtschaftskrise; Russland